Formação e inserção profissional do pedagogo: o panorama histórico desta carreira e os egressos do curso de Pedagogia presencial da Faculdade de Educação da UFMG - Michely de Lima Ferreira Vargas (2016)
The Pedagogy course, throughout its existence, has been the focus of intense discussions that includes questions about the profile of the pedagogy professional: an education specialist, a teacher, or both. The CFE Opinion nº252/69 introduces the qualifications on the Pedagogy Course, that enabled a better definition of the pedagogue activities and a better link of formation and professional performance. Subsequently, the emergence of a democratic conception of the education management contributed to the search for more horizontal ways of of relations among educators. In this context, the pedagogue was criticized due to the idea that its performance in the supervision and inspection would oppose pedagogues as formulators and teachers as implementers. This situation contributed to the intensification of criticism to qualifications, having overpowered the understanding that this model excessively boxed the formation and the performance of the pedagogue. In the 1980s increased the defense by the ANFOPE that the basis of the formation of every educator should be teaching. This view was not consensual, since both amongst researchers and into entities and educational institutions it was possible to find other views, such as the idea that the formation of the pedagogue should be more broader than the preparation for teaching. The CFE Opinion No 252/69 lasted until 2006, when after a long period of discussion, the DCPN defined that teaching in connection with the management and research is the basis of the formation in pedagogy. Considering the historical background and the current context of the Pedagogy course, this thesis aims to examine the relationship between formation and employability of graduates of the local course of FaE UFMG, from 2000 to 2011, focusing on their perceptions about the provision by the disciplines of the fundamentals needed for the professional practice, qualifications and / or processed through additional formations, sectors of performance and the remuneration. The period of analysis has been referenced by the duration of the main legal marks of the course and the curriculum reforms recently made by FaE UFMG. Have been combined quantitative and qualitative procedures for obtaining and analyzing data. This study embraced the analysis of literature about the offer conditions of the pedagogy graduation after approval of DCPN, especially researches that focused curriculum and the socioeconomic profile of undergraduates and studies involving graduates from courses of Pedagogy, in general and specifically the UFMG courses. The research includes a semi structured questionnaire to the graduates and interviews with some of the FaE UFMG teachers who take part on the curriculum reform implemented in 2007. The results showed that the school remains the main sector of activity and that teaching, especially in elementary school, is prevalent, despite the emergence of other areas and activities, especially for distance learning and higher education. The graduates consider, in general, the course provides solid theoretical formation, although they demand a better connection between theory and practice and suggest the inclusion of content designed for the NICT in curriculum. The satisfaction with the activity performed is harmonized with the perception of social devaluation of Pedagogy and the pedagogues. The graduates consider that the pedagogue deserves better earnings and better working conditions.